2004
DOI: 10.1111/j.1095-8339.2004.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Numerical taxonomy study of Salvia sect. Salvia (Labiatae)

Abstract: Multivariate analysis was carried out in order to elucidate the taxonomic relationships between Salvia officinalis L., the type species of the genus, and S. fruticosa Mill., both taxa included in section Salvia (Labiatae). Seventy-five different herbarium specimens from all over the Mediterranean Region, belonging to these two taxa, were analysed. Twenty-four specimens belonging to S. lavandulifolia Vahl. s.l., were used as outgroups. Twenty-six morphological characters were measured and a data matrix was cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 15 publications
0
40
0
1
Order By: Relevance
“…Currently, only Salvia hispanica, and not other species of the genus Salvia, can be grown domestically. To prevent the misidentification of Salvia hispanica and other species of Salvia, a clear understanding of the morphological and genotypical differences among them had been proposed as solutions [3]. Owing to the fact that it can grow in arid environments, it has been highly recommended as an alternative crop for the field crop industry.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only Salvia hispanica, and not other species of the genus Salvia, can be grown domestically. To prevent the misidentification of Salvia hispanica and other species of Salvia, a clear understanding of the morphological and genotypical differences among them had been proposed as solutions [3]. Owing to the fact that it can grow in arid environments, it has been highly recommended as an alternative crop for the field crop industry.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Salvia has been subject to a number of studies based mainly on morphological (Hedge 1982a(Hedge , 1982b, anatomical (Metcalfe & Chalk 1950, 1972), numerical (Reales et al 2004), karyological (Nakipoglu 1993), palynological (Henderson et al 1968), phylogenetical (Walker et al 2004) and evolutionary data (Classen-Bockhoff et al 2004). In addition, the taxonomic importance of the nutlet shape and surface micromorphology of Salvia have been studied by Hedge (1970) and Marin et al (1996).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, considerable confusion in differentiation based on morphology is common between Salvia fruticosa Mill. and Salvia officinalis L. 6 Chemical constituents of some Salvia species have been extensively studied and reviews on these components have been published. 4,5,9 Previous studies indicated that detected variability in chemical constituents of genotypes was under the influence of stages of plant development and inflorescence maturity.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, identification of genotypes in Salvia is complicated owing to the morphological similarity and common occurrence of natural hybridisation within Salvia species. 6,7 In general, identification of genotypes or species in a genus can basically be accomplished using three different approaches: (1) conventional taxonomic studies based on morphological and anatomical characteristics of individuals: 8 (2) chemotyping studies based on chemical constituent differences between individuals:…”
Section: Introductionmentioning
confidence: 99%